2020
DOI: 10.1109/access.2020.3003911
|View full text |Cite
|
Sign up to set email alerts
|

Image Retrieval Scheme Using Quantized Bins of Color Image Components and Adaptive Tetrolet Transform

Abstract: In this paper, a three stage hierarchical image retrieval scheme using a color, texture and shape visual contents (or descriptors) is proposed, since single visual content is not produce an adequate retrieval results effectively. This scheme has reduced the searching space during the image retrieval process at a certain extent due to the hierarchical mode. In Initial stage, the shape feature descriptor has been computed by simple fusion of histograms of gradients and invariant moments of segmented image planes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 67 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…Security implementation is a significant issue in the advanced world, cryptography calculations are one of the approaches to guarantee security [41]- [43]. Focusing on the picture encryption issue in clinical pictures of IoMT application in IoMT based structure [44].…”
Section: Security Measurement and Proposed Lightweight Encryption Algorithmmentioning
confidence: 99%
“…Security implementation is a significant issue in the advanced world, cryptography calculations are one of the approaches to guarantee security [41]- [43]. Focusing on the picture encryption issue in clinical pictures of IoMT application in IoMT based structure [44].…”
Section: Security Measurement and Proposed Lightweight Encryption Algorithmmentioning
confidence: 99%
“…For the experiments and evaluation of our proposed method, the study uses two of the most known image datasets. These two datasets were used widely in many studies related to CBIR and their recent usage found in [26]. First dataset is Corel-1K [27] and has a total of 1000 images divided into ten categories with 100 images for each class.…”
Section: A Images Datasetsmentioning
confidence: 99%
“…In this study, the Corel-1K (Li and Wang, 2008) and GHIM-10K (Liu et al, 2015) datasets were used. These two image datasets have been recently used in Varish et al (2020). The images in the first dataset were divided into ten different categories: Africans, Beaches, Buildings, Buses, Dinosaurs, Elephants, Flowers, Horses, Mountains, and Food.…”
Section: Image Datasetsmentioning
confidence: 99%